(untitled) (International Journal of Engineering and Computer Science, 2017)
Biometrics is the study of automatic techniques for recognizing human beings based on physical or behavioral traits. Among several biometric features, ear is quite stable because it does not vary with age and emotion. It is an important means to guarantee the quality of teaching by the standard and the optimization of the teaching process. Large amounts of data which generated in the process of teaching such as attendance, class performance, homework and testing results and so on are used to process manually. At the same time, there is quite randomness. And it is difficult to accurately reflect the teachers’ working condition. This study explores the use of an Ear Visual Biometric as a measure of identification unit for the Teaching Management System in Universities and Colleges. It is significantly reduces the workload of teachers’ teaching process and improved the credibility and controllability of data by the data acquisition equipment and the whole system. Ear detection and recognition is achieved through the use of Feature Extraction approaches like Force Field Transformation and Chord Point Detection Algorithm is used for better performance than the method to other algorithm.